Finite state transducer based light-weight cryptosystem for data confidentiality in cloud computing. (12th January 2023) - Kodada, Basappa B.; D'Mello, Demian Antony
Cloud computing is derived from parallel, cluster, grid and distributed computing and is becoming an advanced and growing technology. With the rapid growth of Internet technology and its speed, the number of users for cloud is growing enormously and also huge amount of data is also being generated. With the growth of data in cloud, the security and safety of data, like data confidentiality and privacy' is paramount issue because data plays vital role in the current trend. This paper proposes new type of cryptosystem based on the finite state transducer to provide data confidentiality for cloud computing. The paper presents the protocol communication process and gives an insight into security analysis on the proposed scheme. The scheme proves that, it is stronger and more secure than the existing schemes that can be derived from results as proof of concept.